The influence of the Big Five inventory on quality of life in people with Parkinson’s disease aged 50 and above: A Longitudinal Analysis from the Survey of Health, Aging and Retirement in Europe (SHARE) - Sarah Mendorf; Konstantin G. Heimrich; Hannah M. Mühlhammer; Aline Schönenberg; Tino Prell (PLoS ONE, 2025)
Background Parkinson’s disease (PD) significantly reduces quality of life (QoL), particularly due to its complex interplay of motor and nonmotor symptoms. While personality traits influence QoL in chronic diseases, their longitudinal effects in people with PD (PwPD) remain underexplored. This study evaluates the longitudinal predictive influence of neuroticism, conscientiousness, and openness on QoL in PwPD over two waves of the Survey of Health, Aging, and Retirement in Europe (SHARE). Methods This study utilized longitudinal data from 100 PwPD participants in waves 7 and 8 of the Survey of Health, Aging, and Retirement in Europe (SHARE). QoL was assessed using the CASP-12 scale, while personality traits were measured with the Big Five Inventory (BFI-10). Linear regressions and generalized estimating equations (GEE) were used to examine cross-sectional and longitudinal associations between personality traits and QoL, controlling for sociodemographic, psychosocial, and health-related variables. Results Neuroticism was consistently associated with lower QoL across all analyses. Cross-sectional results showed neuroticism as the strongest predictor of QoL decline in wave 7 (beta = -0.33, p < 0.001), and longitudinal GEE analyses confirmed its predictive effect (beta = -0.03, p = 0.007). Conscientiousness and openness showed limited and inconsistent associations with QoL. Beyond personality traits, depressive symptoms and mobility limitations were found to substantially impact QoL, influencing the effects of neuroticism. Conclusions Neuroticism plays a pivotal role in predicting QoL decline in PwPD, highlighting its utility as a target for psychological interventions aimed at emotional regulation and resilience building. While depressive symptoms and mobility limitations also contribute, integrating personality assessments into care strategies may improve outcomes. These findings advocate for a multidimensional approach to managing PD that addresses both clinical and psychological factors.